2002
DOI: 10.1128/iai.70.9.5148-5157.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ageing on the Immunoregulation of Parasitic Infection

Abstract: The plethora of changes associated with immunosenescence radically alters virtually all aspects of immune responsiveness. How this transformation effects resolution of an infectious challenge is addressed in this study. A well-established infection model was used; Trichuris muris, a cecum-dwelling helminth, is natural to mice, and infection in different strains results in clearly polarized responses. A dominating T helper 2 (Th2) response orchestrates immunity, whereas a Th1 response will result in susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
(35 reference statements)
6
24
1
Order By: Relevance
“…For elderly patients, alteration of immunity could be determined as a factor to develop a bigger abscess than for younger patients. This could be explained by the effects of immunosenescence [21]. We have also shown that laboratory findings, especially regarding leucocytosis, C Reactive Protein and hemoglobin, were identical for large and small abscesses.…”
Section: Discussionsupporting
confidence: 60%
“…For elderly patients, alteration of immunity could be determined as a factor to develop a bigger abscess than for younger patients. This could be explained by the effects of immunosenescence [21]. We have also shown that laboratory findings, especially regarding leucocytosis, C Reactive Protein and hemoglobin, were identical for large and small abscesses.…”
Section: Discussionsupporting
confidence: 60%
“…This phenomenon may be caused by the response induced by the p36(LACK) DNA vaccine associated with a change in cytokine production that happens in older mice. Humphreys and Grencis (2002) have shown that older mice (between 19 and 28 months old) are more susceptible to Trichuris muris infection than younger mice (3 months old), and this is associated with a higher IFN-γ and IL-12 production and a lower IL-4 and IL-5 production by lymph node cells. It is possible that the age difference due to the waiting period before the challenge infection may have influenced the cytokine pattern in response to L. chagasi, leading to a stronger type 1 response in older mice.…”
Section: Discussionmentioning
confidence: 98%
“…A prime example of such dysregulation is the increased storage of ROS and impaired apoptosis found in senescent neutrophils as described above. Studies have also suggested that persistent herpes infection, cytomegalovirus (CMV) infection, or parasite antigens may significantly contribute to the increased levels of proinflammatory factors and contribute to a number of negative clinical consequences (62)(63)(64)(65). Together, persistent immunologic dysregulation and abnormal responses to autoantigens may help explain the increased risk of autoimmune diseases in the elderly during immunosenescence, but exactly which factors are most important and what causes these age-associated changes remains largely unclear.…”
Section: Aging-related Changes To the Innate Immune System-associatedmentioning
confidence: 99%